Analisis Governance Support Dan Kompetensi SDM Terhadap Kualitas Pelayanan Dalam Keberlanjutan Usaha Cafe Sawah - Pratama, Yongki; Rizal, Mohammad; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to investigate the impact of Governance support and human resource (HR) competence on service quality in sustaining the business of Cafe Sawah. A descriptive quantitative approach was employed to present the data gathered from questionnaires given to 60 participants, using a saturated sampling method that included all employees at Cafe Sawah. The data were analyzed through multiple regression analysis, showing that both Governance support and HR competence significantly influence service quality at Cafe Sawah when considered together. However, individually, Governance support showed a positive but not significant effect, while HR competence had a positive and significant effect on service quality. The study suggests that Cafe Sawah’s management should focus on improving employee training programs to promote active participation and gather feedback on the governance system. Keywords: Cafe Sawah, Government Support, HR Competency, Service Quality